Geology, landscape and geomorphology: finding the place of geomorphological heritage - Pereira, Paulo (2005)
This work is a contribution for the organisation of geological heritage based on some of the earth sciences disciplines. In this model, geomorphological, paleontological, mineralogical, petrologic, stratigraphic, and tectonic sites must be integrated in their own heritage category.